1997
DOI: 10.1103/physrevb.55.12428
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory biquadratic coupling in Fe/Cr/Fe(001)

Abstract: Polar Kerr measurements have been used to measure the dependence of the biquadratic coupling strength B 12 on Cr thickness in an Fe/Cr/Fe trilayer. The overall behavior, which consists of a maximum coupling strength at d Cr ϭ5 Å ͑3.5 ML͒ with a falloff at greater Cr thicknesses, is found to be consistent with in-plane Kerr and Brillouin light-scattering measurements performed on the same sample. The polar Kerr measurements suggest additionally that B 12 increases from zero near zero Cr thickness, and that it o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Recently, Bruno [4] and Stiles [5] have shown that the coupling can be described in terms of the quantum interference due to spin dependent reflections of Bloch waves at the interfaces. The interest in this subject continues to grow as evidenced by several recent papers [6][7][8][9][10][11][12][13], which cover interesting issues such as the effect of cap layer, ordering in alloy layers, quantum oscillations of spin density, etc.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, Bruno [4] and Stiles [5] have shown that the coupling can be described in terms of the quantum interference due to spin dependent reflections of Bloch waves at the interfaces. The interest in this subject continues to grow as evidenced by several recent papers [6][7][8][9][10][11][12][13], which cover interesting issues such as the effect of cap layer, ordering in alloy layers, quantum oscillations of spin density, etc.…”
mentioning
confidence: 98%
“…The growth optimization will be reported separately [16]. Superlattices (50 periods) with magnetic layer of fixed thickness (t Fe 3 O 4 40 Å) and changing metallic spacer thicknesses (t TiN 5,6,8,10,12,14,16,18,20, and 24 Å) were deposited. These were 1680 0031-9007͞99͞83(8)͞1680(4)$15.00…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] One of the most-studied systems is Fe/Cr, because they exhibit interesting properties like the magnetic interlayer exchange coupling, 3 the giant magnetoresistance 7 and the variable magnitude of the Cr moment. 8 Several experiments have detected these particular properties -polar Kerr measurements in Fe/Cr/Fe (001), 9 Mössbauer spectroscopy. 8 On the other hand, several theoretical calculations exist in the scientific literature where these anomalies are predicted in low-dimensional systems with Fe and Cr 4 and in Cr N clusters embedded in bulk Fe.…”
Section: Introductionmentioning
confidence: 98%
“…Another possible origin of the oscillatory magnetic anisotropy may be biquadratic exchange coupling. 17 Biquadratic coupling could be effective when bilinear coupling diminishes due to interface roughness.…”
mentioning
confidence: 99%